Fish consumption patterns and health risk assessment of polycyclic aromatic hydrocarbons and polychlorinated biphenyls in fried and grilled fish products and mitigation strategies - Abhishek; S. Chakkaravarthi; Tripti Agarwal (Toxicology Reports)
In the present study, the concentration of 13PAHs and the six indicator PCBs was determined through GC-MS/MS in 36 grilled and fried fish products. The study is unique in terms of the simultaneous determination of two types of persistent organic pollutants in grilled and fried fish products. The concentration of ∑13PAHs and ∑6PCBs in these samples varied from 20.80 ± 2.06–947.65 ± 40.85 µg kg−1 and 2.86 ± 0.16–46.52 ± 0.46 µg kg−1, respectively. Dietary exposure and human health risks due to the consumption of fried and grilled fish products for flexitarians, fish-eating population and the entire population were assessed. The incremental lifetime cancer risk (ILCR) estimates for the flexitarians, the entire population, and fish-eating population associated with dietary intake of these products ranged from 4.68 × 10−5 to 1.32 × 10−3, 1.06 × 10−3 to 2.97 × 10−2 and 1.46 × 10−3 to 4.12 × 10−2 respectively. Furthermore, the cancer risk of grilled and fried fish products assessed for the fish-eating population was compared with the cancer risk of raw fish calculated based on the peer-reviewed Indian literature. The mitigation strategies for reduction of PAHs and PCBs in defined fish products have been recommended in the study. The study also highlights the need for in-depth research on PAHs and PCBs formation in grilled and fried fish products.